2020
DOI: 10.1073/pnas.1914186117
|View full text |Cite
|
Sign up to set email alerts
|

IL-4 controls activated neutrophil FcγR2b expression and migration into inflamed joints

Abstract: Neutrophils are the most abundant immune cells found in actively inflamed joints of patients with rheumatoid arthritis (RA), and most animal models for RA depend on neutrophils for the induction of joint inflammation. Exogenous IL-4 and IL-13 protect mice from antibody-mediated joint inflammation, although the mechanism is not understood. Neutrophils display a very strong basal expression of STAT6, which is responsible for signaling following exposure to IL-4 and IL-13. Still, the role of IL-4 and IL-13 in neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 70 publications
3
19
0
1
Order By: Relevance
“…The Hoxb8 cells were generated by transducing BM cells of C57BL/6 Cas9 + GFP + mice with an estrogen-inducible retroviral construct expressing HOXB8 (ER-Hoxb8, a kind gift from Mark P. Kamps, University of California, San Diego) as described [26] , [27] . Transduced BM cells were cultured in 1 µM β-estradiol (BE, Sigma-Aldrich, #E2758) and 25 nM mouse SCF (PeproTech, #250–03) for several weeks with HOXB8 expression turned on to establish a cell line-like population.…”
Section: Methodsmentioning
confidence: 99%
“…The Hoxb8 cells were generated by transducing BM cells of C57BL/6 Cas9 + GFP + mice with an estrogen-inducible retroviral construct expressing HOXB8 (ER-Hoxb8, a kind gift from Mark P. Kamps, University of California, San Diego) as described [26] , [27] . Transduced BM cells were cultured in 1 µM β-estradiol (BE, Sigma-Aldrich, #E2758) and 25 nM mouse SCF (PeproTech, #250–03) for several weeks with HOXB8 expression turned on to establish a cell line-like population.…”
Section: Methodsmentioning
confidence: 99%
“…They observed diminished levels of IL-1β, TNF, IL-8, and prostaglandin E2 (PGE2) in RA ST explants upon the adenovirally delivered IL-4 [ 131 ]. In addition, in a recently performed study with K/BxN serum transfer model and a set of in vitro experiments, it was shown that IL-4 inhibits proinflammatory neutrophils activity and their migration to inflamed joints [ 132 ]. It was also observed that IL-4 displays the capacity to inhibit secretion of IL-11 proinflammatory cytokine by cultured synovial cells obtained from RA patients [ 133 ].…”
Section: Il-4 and Il-13 In Vitro And Ex Vivo Models Of Arthritismentioning
confidence: 99%
“…The Hoxb8 cells were generated by transducing bone marrow cells of C57BL/6 Cas9+ GFP+ mice with an estrogen-inducible retroviral construct expressing HOXB8 (ER-Hoxb8, a kind gift from Mark P. Kamps, University of California, San Diego) as described [29,30]. Transduced BM cells were cultured in 1 µM β-estradiol (BE, Sigma-Aldrich, #E2758) and 25 nM mouse SCF (PeproTech, #250-03) for several weeks with HOXB8 expression turned on to establish a cell line-like population.…”
Section: Sgrna and Primer Designmentioning
confidence: 99%